Securing reform? Post-election power sharing and security sector reform in Zimbabwe, Kenya, and Togo, 2006-2013 - Noyes, A (2017)
Power-sharing arrangements have become the default tool of international actors to resolve a vast range of conflicts worldwide, with a particular concentration in sub-Saharan Africa. Traditionally used to end high-intensity civil wars, recently power sharing has increasingly been used to terminate an array of lower-intensity conflicts, such as election-related violence in Togo in 2006 and Kenya and Zimbabwe in 2008. The thin but emerging scholarship on post-election power sharing is largely negative, maintaining that the model is unlikely to deliver the institutional reforms necessary to resolve the underlying roots of electoral conflicts. Yet the cases of Kenya, and, to a lesser extent, Togo, appear to complicate this narrative, suggesting that post-election power sharing may be able to deliver some key but thorny institutional reforms, such as security sector reform. While the power-sharing model continues to be used worldwide and security reform is widely identified by scholars and practitioners as critical to durable peace, the existing literature has generally ignored the potential link between the two. As such, this dissertation seeks to answer the following questions: Does post-election power sharing lead to security sector reform? Which causal factors are most important in shaping security reform outcomes under post-election power sharing, and through what processes or mechanisms? The two-step integrated theoretical framework presented here forwards a structured contingency approach, positing that a combination of long- and short-term domestic and international factors will drive or stymie reform of the security sector under post-election power sharing in democratizing countries. In short, the theory argues that two main longterm factors, the nature of civil-military relations and the character of external involvement, combined with two short-term mechanisms, the design of the political agreement and the type of political strategy deployed by the parties, will be the most important factors shaping security reform outcomes under post-election power sharing. I demonstrate that post-election power sharing plays a significant role in the causal process of security reform and can deliver some institutional reforms, under certain conditions. The dissertation uses the method of structured, focused comparison to build and apply the theoretical propositions to the cases of Kenya, Togo, and Zimbabwe. Using process tracing and the logic of most-similar comparisons, I conduct two sets of cross- and within-case comparisons, utilizing elite interviews as the primary tool for data collection. I conducted over 100 interviews with key decision-makers in my case countries—including former prime ministers, cabinet ministers, top political party leaders, senior security officials, and international stakeholders.